2016
DOI: 10.15537/smj.2016.3.11388
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of oral cancer in Arab countries

Abstract: Objectives:To review the oral cancer (OC) studies that were conducted in Arab countries with regard to epidemiology, risk factors, and prognosis.Methods:A computer-based PubMed literature search was performed to retrieve studies conducted in the Arab world on epidemiology of OC. After screening for exclusion criteria, cross-referencing, and searching local journals, a total of 19 articles were included.Results:Eight prevalence studies found an OC prevalence ranging from 1.8 to 2.13 per 100,000 persons. Oral ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
77
2
9

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 102 publications
(95 citation statements)
references
References 27 publications
(46 reference statements)
7
77
2
9
Order By: Relevance
“…Two-thirds of our cases were presented in advanced stages. This is concordant with the findings in other studies in different geographical areas [12,13,[20][21][22]. However, some studies, especially from the western world, showed a higher percentage of early diseases [10,23,24].…”
Section: Survival Outcomessupporting
confidence: 92%
See 1 more Smart Citation
“…Two-thirds of our cases were presented in advanced stages. This is concordant with the findings in other studies in different geographical areas [12,13,[20][21][22]. However, some studies, especially from the western world, showed a higher percentage of early diseases [10,23,24].…”
Section: Survival Outcomessupporting
confidence: 92%
“…Also, another study from Saudi Arabia showed 45% of oral cancer cases were of primary tongue origin [11]. In a recent review analysis of oral cancer in different Arab countries, tongue was the most common primary tumor site [12]. This is not the case among Asian populations.…”
Section: Resultsmentioning
confidence: 99%
“…Oral cancer (OC) is one of the global diseases, which occupies the eighth rank among different types known of cancers (Petersen, Bourgeois, Ogawa, Estupinan‐Day, & Ndiaye, ; Razavi, Zolfaghari, Foroohandeh, Doost, & Tahani, ). Annually, the estimated number of OC new cases exceeds 300.000 cases (Al‐Jaber, Al‐Nasser, & El‐Metwally, ). Although the diverse distribution of the disease incidence worldwide, the number of new cases demonstrates increase in developing countries (Lopez‐Jornet, Camacho‐Alonso, & Molina‐Minano, ).…”
Section: Introductionmentioning
confidence: 99%
“…The authors of an extended systematic review of oral cancer in Arab countries were able to associate cancer incidence with water‐pipe smoking only in part. Nevertheless, commonly detected cancer of the tongue, floor of the mouth, and lower lip was attributed to the socio‐cultural behavior of the study population which would include water‐pipe usage . There are also publications about association of tumors outside the respiratory tract with water‐pipe smoking.…”
Section: Cancer Risks Associated With Smokingmentioning
confidence: 99%